Caries and Body Mass Index, What Relation? - Sousa, Sofia Cochito (2019)
Introduction: The prevalence of overweight and obesity is increasing in pediatric age and that is traditionally associated with worse oral health. However, in the literature this association is controversial. We intend to characterize the prevalence of overweight, obesity and caries in a pediatric population and check for an association between caries and body mass index. Methods: Retrospective study of children aged 5 years or older, followed in a primary care unit in Lisbon. Demographic data such as age and sex, anthropometric data (height, weight and body mass index with percentile) and presence or absence of caries were analyzed. Results: A sample of 1,398 children with an average age of 9.96 ± 3.39 years at the last visit was obtained, without gender predominance. In relation to the body mass index percentile, 3.1% had < 3, 72.0% between 3-85, 14.7% between 85-97 and 10.2% > 97. Only 730 clinical records referenced oral health, with a caries prevalence of 59.5%. There was a statistically significant association between the body mass index percentile < 3 and caries (p = 0.004; odds ratio 4.27, confidence interval 95% 1.47-12.48) that was independent of age. Discussion: These results reveal that approximately one in four children are overweight or obese and three in five have caries. Body mass index percentiles < 3 are associated with a higher prevalence of caries. It is vital to continue to promote healthy lifestyles in all primary care consultations.